The mutational analysis of mitochondrial DNA in maternal inheritance of polycystic ovarian syndrome - Bibi, Shaheen; Abbas, Ghulam; Khan, Muhammad Zahoor; Nawaz, Tanzeela; Ullah, Qudrat; Uddin, Aziz; Khan, Muhammad Fiaz; Ghafoor, Sajid Ul; Nadeem, Muhammad Shahid; Tabassum, Sadia; Zahoor, Muhammad (Frontiers in Endocrinology, 2023)
The incidence of Polycystic Ovarian Syndrome (PCOS) is increasing globally, and it is recognized as a leading cause of infertility in women. Besides environmental factors, maternal genetics plays a significant role in the development of PCOS. To date, no conclusive predisposition test is available for PCOS. Therefore, our aim is to identify novel maternal genetic risk factors for PCOS by studying the genomes of patients from Pakistan. We used Next-Generation Sequencing (NGS) to sequence the entire mitochondrial DNA of three PCOS patients and analyzed it for mutations. We employed MitoTIP (Mitochondrial tRNA Informatics Predictor) and PON-mt-tRNA to identify variations in the mitochondrial DNA. Our analysis revealed six regions with common variations in all three genomes, including the genes MT-RNR1 (mitochondrially encoded 12S RNA) MT-RNR2 (Mitochondrially encoded 16S RNA) MT-ATP6 (mitochondrially encoded ATP synthase 6), MT-TL2 (mitochondrially encoded tRNA leucine 2), and MT-CYTB (mitochondrially encoded cytochrome b). Individual variations were also observed. The D-loop region showed the highest frequency of mutations, followed by the non-coding regions of RNR1 and RNR2 genes. We also detected two frameshifts in mitochondrially encoded NADH Dehydrogenase 2 (MT-ND2) and mitochondrially encoded NADH Dehydrogenase 5 (ND5) genes in the individual genomes. We conducted a score-based pathogenicity analysis of these mitochondrial variants using MitoTIP and PON-mt-tRNA. The analysis revealed that most of the variants were likely to result in benign cysts; however, the frameshift mutations in the ND2 gene were associated with a high risk of complications and pathogenicity of PCOS. Our study has unveiled variations in mitochondrial DNA that could be associated with the development of PCOS and potential predisposition tests. This is the first report of these mutations and their association with PCOS.